2023
DOI: 10.1680/jstbu.20.00150
|View full text |Cite
|
Sign up to set email alerts
|

Failure mode of deteriorated concrete tunnel sections under subsidence and localised shear

Abstract: It is frequently reported that groundwater containing salt flowing into underground reinforced concrete structures results in steel reinforcement corrosion. However, little has been done to study the impact of such chloride-induced deterioration on structural performance when an external load acts on the underground structure, such as ground subsidence or the movement related to faults. In this study, structural experiments and finite-element analysis of the interaction between an underground structure and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…For a large scale, the underground RC tunnel inside soil foundation exposed to stray current was modeled, and the soil electrolyte was charged to create the entire electrical field to reproduce the stray current. Testing on the specimen with intermediate dimensions and circular shape had been conducted previously (Aoki et al 2021), where the most severe anodic and cathodic regions were found to lie on the charging direction (see Fig. 3).…”
Section: Simulation Modelsmentioning
confidence: 99%
“…For a large scale, the underground RC tunnel inside soil foundation exposed to stray current was modeled, and the soil electrolyte was charged to create the entire electrical field to reproduce the stray current. Testing on the specimen with intermediate dimensions and circular shape had been conducted previously (Aoki et al 2021), where the most severe anodic and cathodic regions were found to lie on the charging direction (see Fig. 3).…”
Section: Simulation Modelsmentioning
confidence: 99%